Secondary structures of carbon nanotubes and sulfur-carbon composites containing the same
The development of a flower-like secondary structure of carbon nanotubes addresses the ion diffusion and kinetic activity challenges in lithium sulfur batteries, resulting in high energy density and improved performance.
Patent Information
- Application Number
- JP2024563415
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-28
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-08-28
AI Technical Summary
Existing lithium sulfur batteries face challenges with insufficient ion diffusion paths and low kinetic activity of sulfur oxidation/reduction reactions due to the use of carbon nanotubes with limited specific surface area and porosity.
A secondary structure of carbon nanotubes with a flower-like shape, featuring a spherical core and amorphous flakes, is developed to enhance the specific surface area and ion diffusion paths, thereby supporting a sulfur-carbon composite as a positive electrode active material in lithium sulfur batteries.
The novel secondary structure of carbon nanotubes significantly improves the kinetic activity of sulfur oxidation/reduction reactions and ensures sufficient ion diffusion, leading to high energy density lithium sulfur batteries with enhanced performance.
Smart Images

Figure 2025514229000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a secondary structure of carbon nanotubes that can be used as a porous carbon material for electrodes of electrochemical devices, and a method for producing the same.
[0002] In particular, the present invention relates to a sulfur-carbon composite in which sulfur is supported on the secondary structure of carbon nanotubes, and a lithium-sulfur battery containing the same.
[0003] This application claims priority to Korean Patent Application No. 10-2022-0110402 filed on August 31, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]
[0004] Lithium-sulfur batteries are battery systems that use sulfur-based materials with sulfur-sulfur bonds as the positive electrode active material and lithium metal as the negative electrode active material. Sulfur, the main material of the positive electrode active material, has the advantages of being abundant worldwide, non-toxic, and having a low atomic weight.
[0005] As the application of secondary batteries expands to electric vehicles (EVs) and energy storage systems (ESS), lithium-sulfur battery technology is gaining attention because it can theoretically realize a high "energy storage density per weight (up to 2,600Wh / kg)" compared to lithium-ion secondary batteries, which have a relatively low "energy storage density per weight (up to 250Wh / kg)."
[0006] During discharge, lithium, the negative electrode active material, is oxidized by giving out electrons and ionized into lithium cations, while the positive electrode active material, the sulfur-based material, is reduced by receiving electrons. Here, the S-S bond receives two electrons and is converted into sulfur anion form by the reduction reaction of the sulfur-based material. The lithium cations generated by the oxidation reaction of lithium are transferred to the positive electrode by the electrolyte, and combine with the sulfur anions generated by the reduction reaction of the sulfur-based compound to form a salt. Specifically, sulfur before discharge has a ring-shaped S8 structure, which is converted into lithium polysulfide (Li2Sx) by the reduction reaction, and is completely reduced to generate lithium sulfide (Li2S).
[0007] Thus, the sulfur used in the positive electrode active material is 5×10 -30 Since sulfur is a non-conductive insulator with an electrical conductivity of 1000 S / cm, research is being conducted on cathode materials that combine sulfur with conductive materials to transfer electrons during electrochemical reactions, i.e., to give sulfur reactivity, in order to use it as an active material. In order to improve the kinetic activity of electrochemical reactions during charging and discharging of lithium-sulfur secondary batteries, there is a continuous demand for technological development of sulfur-carbon composites, in which cathode active materials are supported on porous carbon materials, as cathode materials.
[0008] As an example, the development of materials using carbon nanotubes (CNTs) as porous carbon materials is progressing. CNTs are highly porous materials and have the advantage of being able to increase the amount of sulfur carried, but they have the problem that they do not provide sufficient ion permeation paths for manufacturing electrodes, and they have low ion diffusivity. In addition, in order to develop high-energy-density lithium-sulfur secondary batteries, it is necessary to develop sulfur-carbon composites that can realize low-porosity electrodes.
[0009] For this purpose, it is required that the porous carbon material has a high specific surface area and a sufficient ion diffusion path so that the sulfur and electrolyte can be easily transferred. Summary of the Invention [Problem to be solved by the invention]
[0010] The problem to be solved by the present invention is as follows: The object of the present invention is to provide a secondary structure of carbon nanotubes having a large specific surface area and a novel shape that can ensure sufficient ion diffusion paths in an electrode when used as a support for an active material.
[0011] In addition, we aim to provide a sulfur-carbon composite in which the secondary structure of carbon nanotubes having the novel shape is used as a support for an active material and sulfur (S8) is composited as the active material, thereby providing a sulfur-carbon composite with increased kinetic activity in the oxidation / reduction reaction of sulfur.
[0012] It is yet another object of the present invention to provide an electrode for an electrochemical device, which includes a secondary structure of carbon nanotubes having the novel shape, and an electrochemical device including the electrode.
[0013] In particular, the present invention provides a lithium-sulfur battery positive electrode comprising the sulfur-carbon composite having the secondary structure of carbon nanotubes as a positive electrode active material, and a lithium-sulfur battery including the same, and further provides a lithium-sulfur battery having a high energy density by implementing an electrode with low porosity using the sulfur-carbon composite. [Means for solving the problem]
[0014] In order to achieve the above objectives, According to one aspect of the present invention, there is provided a secondary structure having the following embodiment:
[0015] The secondary structure according to the first embodiment is The carbon nanotubes are aggregated into a secondary structure, and have a flower-like structure including a spherical core and at least one amorphous flake on the surface of the core.
[0016] According to the second embodiment, in the first embodiment, The specific surface area of the secondary structure is 50 m 2 / g~1,000m 2 / g.
[0017] According to the third embodiment, in the first or second embodiment, The average particle size D of the secondary structures 50 can be from 1 μm to 100 μm.
[0018] According to a fourth embodiment, in any one of the first to third embodiments, The secondary structures have an average particle size D of 10 to 20 μm. 50 A spherical core having an average particle size D of 1 to 5 μm on the surface of the core. 50 and at least one amorphous flake having the formula:
[0019] According to a fifth embodiment, in any one of the first to fourth embodiments, The secondary structures may have a sphericity of 0.5 to 0.99.
[0020] According to a sixth embodiment, in any one of the first to fifth embodiments, The total pore volume in the secondary structure is 0.5 to 5 cm 3 / g.
[0021] According to the seventh embodiment, in any one of the first to sixth embodiments, The carbon nanotubes may have a diameter of 50 to 500 nm and a length of 0.1 to 5 μm.
[0022] According to an eighth embodiment, in any one of the first to seventh embodiments, The carbon nanotubes may have a diameter to length ratio of 1:1 to 1:30.
[0023] According to another aspect of the present invention, there is provided a method for manufacturing a secondary structure, the following embodiments of which are given below.
[0024] A method for manufacturing a secondary structure according to a ninth embodiment includes: (S10) aggregating the carbon nanotubes to obtain entangled macro carbon nanotubes; (S20) obtaining a secondary structure having a modified structure from the entangled giant carbon nanotubes; The secondary structures may have a flower-like structure comprising a spherical core and at least one amorphous flake on the surface of the core.
[0025] According to the tenth embodiment, in the ninth embodiment, The specific surface area of the secondary structure is 50 m 2 / g~1,000m 2 / g.
[0026] According to the eleventh embodiment, in the ninth or tenth embodiment, In the step S10, the dispersion in which the carbon nanotubes are dispersed in a first dispersion medium may be spray-dried.
[0027] According to the twelfth embodiment, in any one of the ninth to eleventh embodiments, The step S20 may be a step of spray-drying the dispersion in which the entangled giant carbon nanotubes are dispersed in a second dispersion medium.
[0028] According to the thirteenth embodiment, in any one of the ninth to twelfth embodiments, The first dispersion medium or the second dispersion medium may include water, alcohol, benzene, toluene, pyridine, acetone, tetrahydrofuran (THF), dimethylformaldehyde (DMF), or two or more of these.
[0029] According to the 14th embodiment, in any one of the 9th to 13th embodiments, The method may further include a step of carbonizing after the spray drying.
[0030] According to the fifteenth embodiment, in any one of the ninth to fourteenth embodiments, The carbonization may be carried out at a temperature of 500°C to 1,200°C.
[0031] According to the sixteenth embodiment, in any one of the ninth to fifteenth embodiments, The method may further include a step of chopping the carbon nanotubes before the step S10, and in the step S10, entangled giant carbon nanotubes are obtained from the chopped carbon nanotubes.
[0032] According to the seventeenth embodiment, in any one of the ninth to sixteenth embodiments, The entangled giant carbon nanotubes may have a sphericity of 0.5 to 0.99.
[0033] According to the eighteenth embodiment, in any one of the ninth to seventeenth embodiments, The tangled giant carbon nanotubes have an average particle size D of 20 to 200 μm. 50 may have:
[0034] According to the 19th embodiment, in any one of the 9th to 18th embodiments, The entangled giant carbon nanotubes may have a porosity of 60-90% by volume.
[0035] According to the twentieth embodiment, in any one of the ninth to nineteenth embodiments, The giant tangled carbon nanotube is 200m long. 2 / g~400m 2 / g.
[0036] According to still another aspect of the present invention, there is provided a sulfur-carbon composite according to the following embodiment.
[0037] The sulfur-carbon composite according to the twenty-first embodiment is The secondary structure according to any one of the first to eighth embodiments may include a sulfur-containing compound supported on at least a portion of the interior and exterior surfaces of the pores of the secondary structure.
[0038] According to the twenty-second embodiment, in the twenty-first embodiment, The sulfur-containing compound may include inorganic sulfur (S8), lithium polysulfide (Li2Sn, 1≦n≦8), carbon-sulfur polymer (C2Sx)m, 2.5≦x≦50, 2≦m), or mixtures thereof.
[0039] According to the 23rd embodiment, in the 21st or 22nd embodiment, The weight ratio of the secondary structure and the sulfur-containing compound may be 10:90 to 40:60.
[0040] According to another aspect of the present invention, there is provided an electrode according to the following embodiment.
[0041] The electrode according to the twenty-fourth embodiment is The electrode active material layer may include the secondary structure according to any one of the first to eighth embodiments.
[0042] According to still another aspect of the present invention, there is provided an electrochemical device according to the following embodiment.
[0043] The electrochemical device according to the twenty-fifth embodiment includes: The battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte solution, At least one of the positive electrode and the negative electrode may include the secondary structure according to any one of the first to eighth embodiments. Effect of the Invention
[0044] According to one embodiment of the present invention, It is possible to provide carbon nanotube secondary structures having novel shapes.
[0045] In particular, it is possible to provide a secondary structure of carbon nanotubes that has a high specific surface area and a controlled pore structure, thereby improving the ion diffusion pathway when used in an electrode and exhibiting high electrochemical activity, and a composite in which an active material is combined with the secondary structure.
[0046] In particular, the sulfur-carbon composite in which sulfur (S8) is compounded with the secondary structure of the carbon nanotube provides excellent kinetic activity in the oxidation / reduction reaction of sulfur. For example, the sulfur-carbon composite has a high specific surface area, which increases the number of active sites where sulfur can participate in the reaction, thereby increasing the reactivity of sulfur. In addition, the sulfur-carbon composite has a large pore volume, which makes it easy to support sulfur and provides a favorable effect in securing an ion diffusion path.
[0047] An electrode using the sulfur-carbon composite as a positive electrode active material can realize an electrode with low porosity, thereby providing a lithium-sulfur secondary battery with high energy density.
[0048] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited to only the matters described in the drawings. [Brief description of the drawings]
[0049] [Figure 1] 1 is a SEM (scanning electron microscopy) photograph of a secondary structure of Comparative Example 1 in the present specification. [Diagram 2] 1 is a SEM photograph of the secondary structure of Example 1 herein. [Diagram 3] FIG. 2 is a high-magnification SEM image of the sulfur-carbon composite of Comparative Example 2 herein. [Figure 4] FIG. 2 is a low-magnification SEM image of the sulfur-carbon composite of Comparative Example 2 herein. [Diagram 5] FIG. 2 is a high-magnification SEM image of the sulfur-carbon composite of Example 2 herein. [Figure 6] FIG. 2 is a low-magnification SEM image of the sulfur-carbon composite of Example 2 herein. [Figure 7] 1 is a graph showing charge / discharge evaluation results of lithium-sulfur coin cells prepared using positive electrodes to which the sulfur-carbon composite of Comparative Example 2 and the sulfur-carbon composite of Example 2 were applied, according to an Experimental Example herein. [Figure 8] 1 is a graph showing the results of evaluating the life span of lithium-sulfur coin cells fabricated using positive electrodes to which the sulfur-carbon composite of Comparative Example 2 and the sulfur-carbon composite of Example 2 were applied, according to an Experimental Example herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0050] The present invention will be described in detail below. However, the present invention is not limited to the following content, and each component may be modified in various ways or mixed selectively as necessary. Therefore, it should be understood that all modifications, equivalents, or alternatives included in the spirit and technical scope of the present invention are incorporated.
[0051] In the present specification, when a certain configuration "includes" a certain component, it does not mean that other components are excluded, but that other components may be further included, unless otherwise specified.
[0052] In this specification, the phrase "A and / or B" means A or B, or all of them.
[0053] According to one aspect of the present invention, a porous carbon material that can be used as an electrode material for an electrochemical device is provided. Specifically, a secondary structure of carbon nanotubes having a novel shape is provided. Such a secondary structure has a high specific surface area and a unique pore structure. Therefore, when the secondary structure is applied to an electrode, it is advantageous to realize an electrode with low porosity, and therefore an electrochemical device with high energy density can be provided.
[0054] In particular, the carbon nanotube secondary structure can be used as a support for a positive electrode active material of a lithium-sulfur battery, and can be mixed and composited with inorganic sulfur (S8) to provide a sulfur-carbon composite usable as a positive electrode active material of a lithium-sulfur battery. However, the carbon nanotube secondary structure can be used not only as a support for the active material of the lithium-sulfur battery, but also as a conductive additive for an electrode of an electrochemical device, and the use of the carbon nanotube secondary structure is not limited thereto.
[0055] According to one aspect of the present invention, a carbon nanotube secondary structure usable as a material for a positive electrode of a lithium-sulfur battery is provided. Specifically, the secondary structure has a structure including an outer surface and a plurality of pores inside. In this case, the secondary structure can be used as a porous carbon material for supporting a sulfur-containing compound as a positive electrode active material on at least one of the outer surface and / or the inner surface of the pores, but the use of the present invention is not limited thereto.
[0056] The secondary structure according to one embodiment of the present invention is a secondary structure formed by agglomeration of carbon nanotubes, and has a flower-like structure including a spherical core and at least one amorphous flake(s) on the surface of the core.
[0057] In one embodiment of the present invention, the secondary structure may be characterized in that it exhibits a large specific surface area, thereby increasing active sites at which sulfur can participate in an oxidation / reduction reaction when supporting a sulfur-containing compound, which is a positive electrode active material, but the present invention is not limited thereto.
[0058] In one embodiment of the present invention, the secondary structure has a large pore volume, which makes it easy to support a sulfur-containing compound as a positive electrode active material and is advantageous in ensuring an ion diffusion path, but the present invention is not limited thereto.
[0059] As described below, the secondary structure according to one aspect of the present invention may be formed by aggregating and redispersing carbon nanotubes that are shorter than conventional carbon nanotubes, for example, carbon nanotubes that have been cut into small pieces to shorten their length, i.e., carbon nanotubes with a smaller ratio of length to diameter than conventional carbon nanotubes. This allows the formation of a gigantic secondary structure having a higher sphericity and a larger specific surface area than when conventional carbon nanotubes with a very high ratio of length to diameter are aggregated. The carbon composite has an effect of having a large specific surface area while sufficiently securing ion diffusion paths by redispersing the formed gigantic secondary structure and transforming the structure into a flower-like shape.
[0060] In the present specification, the flower-like structure refers to a morphology having a spherical core and at least one amorphous flake formed on the surface of the core.
[0061] 1 and 2 are SEM images of different shapes of carbon nanotube secondary structures. Specifically, Fig. 1 shows a carbon nanotube secondary structure formed simply to have a spherical shape, and Fig. 2 shows a carbon nanotube secondary structure formed to have a flower-like structure having a spherical core and at least one amorphous flake formed on the surface of the core according to one embodiment of the present invention.
[0062] Referring to FIG. 1, it can be seen that the carbon nanotubes are aggregated to have a spherical shape to form the secondary structure, and that the spherical surface of the secondary structure is formed relatively smoothly.
[0063] Meanwhile, referring to FIG. 2, it can be seen that the carbon composite has a flower-like structure in which a spherical core and at least one plate-like flake are formed on the surface of the core, and thus a plurality of concave and convex portions are formed on the spherical surface of the secondary structure.
[0064] In this specification, the core portion of the secondary structure is said to be "spherical" not only to mean a perfect sphere, but also to mean a similar sphere such as an ellipse or doughnut shape having a partially different radius.
[0065] In this specification, the "amorphous flakes" formed on the surface of the core portion of the secondary structure are formed by spray-drying a dispersion of carbon nanotubes, redispersing them, and then spray-drying them a second time, as described below, and are a collective term for the structures formed on the surface of the core portion, each of which has a granular shape smaller than the size of the core portion.
[0066] In one embodiment of the present invention, the secondary structure may have the following physical properties. When the secondary structure has the following physical properties, it may have an advantageous effect in improving the performance of the battery, but the present invention is not limited thereto.
[0067] In one embodiment of the present invention, the secondary structure is formed by agglomerating carbon nanotubes and may have a large specific surface area. For example, the specific surface area of the secondary structure is 50 m 2 / g~1,000m 2 / g, specifically 100m 2 / g~500m 2 / g, more specifically 150m 2 / g~200m 2 / g.
[0068] In the present specification, the specific surface area refers to a BET specific surface area value measured by the BET method, and the BET specific surface area can be measured by a known method for measuring the BET specific surface area. For example, the BET specific surface area can be a value calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using BELSORP-max from BEL Japan.
[0069] In one embodiment of the present invention, the secondary structure has a large specific surface area due to the aggregation of carbon nanotubes, but the particle size may be adjusted to be smaller than a giant particle exceeding 100 μm, specifically, 50 μm, in order to realize an electrode with low porosity. For example, the average particle size D 50 can be 1 to 100 μm, specifically 1 to 50 μm, 5 to 50 μm, 10 to 100 μm, 10 to 50 μm, 12 to 100 μm, 12 to 50 μm, more specifically 10 to 30 μm or 10 μm to 20 μm.
[0070] In the present specification, the particle size can be measured by scanning electron microscopy (SEM), field emission scanning electron microscopy (FE-SEM), or laser diffraction method. The measurement using the laser diffraction method can be performed using, for example, a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000).
[0071] In this specification, the average particle size D 50 means the particle size at the 50% point of the cumulative diameter distribution.
[0072] In one embodiment of the present invention, the secondary structure having a flower-like structure has an average particle size D of 10 to 20 μm. 50 A spherical core having an average particle size D of 1 to 5 μm, specifically 1 to 3 μm, on the surface of the core. 50Specifically, the flake may have an average particle size D of 10 to 20 μm. 50 The surface of the spherical core has an average particle size D of 1 to 5 μm, specifically 1 to 3 μm. 50 The morphology may include a plurality of amorphous flakes having the following structure:
[0073] In this case, the size of the spherical core portion can be measured using the above-mentioned laser diffraction particle size measuring device, and the size of the amorphous flakes indicates the length of the longest axis in a single flake. When the secondary structure has the above-mentioned form, it can have an advantageous effect on improving the performance of an electrode and a battery to which it is applied, but the present invention is not limited thereto.
[0074] In one embodiment of the present invention, the secondary structures may have a roundness of, for example, 0.5 to 0.99. Specifically, the roundness of the secondary structures may be 0.6 to 0.95, more specifically, 0.7 to 0.9. The secondary structures are formed by redispersing entangled giant carbon nanotubes that are spherical due to aggregation of carbon nanotubes, as described below, and may have the effect of providing uniform reactivity in the electrode by maintaining a high roundness level of the entangled giant carbon nanotubes, but the present invention is not limited thereto.
[0075] In the present specification, the sphericity of the secondary structure is calculated by measuring the length of the minor axis and the major axis from the overall shape of one of the secondary structures, and then dividing the length of the major axis by the length of the minor axis. In this case, the minor axis and the major axis can be measured by the same method as the method for measuring the size of a particle.
[0076] Sphericity = [(length of major axis of secondary structure) / (length of shortening of secondary structure)]
[0077] In one embodiment of the present invention, the secondary structure is formed by agglomerating the carbon nanotubes and includes a plurality of pores inside the secondary structure. For example, the total volume of the pores of the secondary structure is 0.5 to 5 cm. 3 / g, specifically 0.5 to 3 cm3 / g, more specifically 0.8-2 cm 3 When the total volume of the pores of the secondary structure is within the above-mentioned range, the sulfur loading amount of the sulfur-carbon composite using the secondary structure is excellent and an electrode having excellent packing density can be provided, which is advantageous in providing a battery having a high energy density, but the present invention is not limited thereto.
[0078] In this specification, the total pore volume of the secondary structure can be measured, for example, by the BET (Brunauer-Emmett-Teller) method using nitrogen gas or by a mercury porosimeter and ASTM D-2873.
[0079] In one embodiment of the present invention, the carbon nanotube, which is the primary particle constituting the secondary structure, may have a diameter of, for example, 50 to 500 nm, specifically 75 to 350 nm, more specifically 100 to 200 nm. The diameter of the carbon nanotube may be a passage for the movement of sulfur and electrolyte in the sulfur-carbon composite, so that when the carbon nanotube has a diameter in the above range, it may have an advantageous effect on sulfur loading and mass transfer of the electrolyte, but the present invention is not limited thereto.
[0080] Unless otherwise specified in this specification, the diameter of the carbon nanotube may be measured using a transmission electron microscope (TEM), and the length of the carbon nanotube may be measured using a scanning electron microscope (SEM), but the measurement methods are not limited thereto.
[0081] In one embodiment of the present invention, the carbon nanotube may have a length of, for example, 0.1 to 5 μm, specifically 0.2 to 4 μm, more specifically 0.3 to 3 μm. The length as well as the diameter of the carbon nanotube may affect the accessibility of the material to the inside of the secondary structure, and the length of the carbon nanotube may affect the outer shape of the secondary structure. Specifically, when the length of the carbon nanotube is within the above range, the sphericity and porosity of the final secondary structure are increased, and thus the migration paths of sulfur and electrolyte are sufficiently secured within the final secondary structure, which is advantageous for sulfur loading and electrolyte material transfer.
[0082] In accordance with the above, in an embodiment of the present invention, not only the diameter and length of the carbon nanotubes constituting the secondary structure, but also the ratio of the diameter and the length may be important. In one embodiment of the present invention, the ratio of the diameter and the length of the carbon nanotubes may be 1:1 to 1:30, specifically 1:3 to 1:25, and more specifically 1:5 to 1:20.
[0083] A method for producing a secondary structure by agglomerating the above-mentioned carbon nanotubes will be described below.
[0084] A method for manufacturing a secondary structure according to another aspect of the present invention includes the steps of (S10) obtaining a tangled giant carbon nanotube from a carbon nanotube, and (S20) obtaining a secondary structure having a modified structure from the tangled giant carbon nanotube, wherein the secondary structure has a flower-like structure including a spherical core and at least one amorphous flake on a surface of the core.
[0085] In one embodiment of the present invention, the secondary structure has a specific surface area of 50 m2 as described above. 2 / g~1,000m 2 In addition, it has the physical properties of the secondary structure described above.
[0086] In order to obtain the secondary structure, first, (S10) a step of granulating the carbon nanotubes as the primary particles to obtain giant entangled carbon nanotubes is carried out.
[0087] In an embodiment of the present invention, step S10 may include preparing a dispersion of carbon nanotubes, particularly, spray-drying the dispersion in which the carbon nanotubes are dispersed.
[0088] In the present specification, the dispersion medium for preparing the carbon nanotube dispersion is referred to as a first dispersion medium to distinguish it from the dispersion medium in step S20 described below. The first dispersion medium may include, but is not limited to, water, alcohol, benzene, toluene, pyridine, acetone, tetrahydrofuran (THF), dimethylformaldehyde (DMF), or two or more of these.
[0089] In one embodiment of the present invention, the dispersion liquid may further include a known dispersant to improve the dispersibility of the carbon nanotubes. The dispersant may be, for example, but is not limited to, polystyrene sulfonate, polyacrylic acid, polyvinylpyrrolidone, polyvinyl alcohol, carboxymethyl cellulose, polyethylene oxide, polyvinyl butyral, ethyl cellulose, or a mixture of two or more thereof. The dispersant may not remain in the secondary structure obtained by the carbonization process in the subsequent step of obtaining the secondary structure.
[0090] In an embodiment of the present invention, the carbon nanotubes may be contained in an amount of 0.5 to 5 wt % based on the total weight of the carbon nanotube dispersion liquid. When the dispersion liquid further contains the dispersant, the weight ratio of the carbon nanotubes to the dispersant may be, for example, 1:10 to 1:20, but the present invention is not limited thereto.
[0091] In one embodiment of the present invention, step S10 may include a spray-drying step in order to aggregate the carbon nanotubes and granulate them into large secondary structures. The spray-drying method may be performed by supplying the carbon nanotube dispersion into a sprayer, forming droplets by spraying, and then drying the droplets. In this case, the spray-drying apparatus may include a sprayer (droplet generating device), a reactor, and a collector, but the present invention is not limited thereto.
[0092] In one embodiment of the present invention, the spray drying in step S10 may be performed, for example, at room temperature and pressure, by spraying, pressurized spraying, or electrostatic spraying, and is not particularly limited in the present invention. In one example, pressurized spraying is a method in which a dispersion is pressurized and sprayed from a pressurized sprayer to form droplets, and then particles are produced using a diffusion dryer. Also, electrostatic spraying is a method in which droplets are formed using an electrostatic spray nozzle using a high voltage generator, and then particles are produced using a diffusion dryer.
[0093] In one embodiment of the present invention, in step S10, chopped carbon nanotubes may be used to chop conventional carbon nanotubes to use short carbon nanotubes. For this purpose, a step of chopping carbon nanotubes may be further included before step S10, and the chopped carbon nanotubes may be used as primary particles in step S10.
[0094] In an embodiment of the present invention, the carbon nanotubes may be chopped by, for example, a ball mill method.
[0095] In an embodiment of the present invention, the chopped carbon nanotubes may have a diameter of, for example, 50 to 500 nm and a length of, for example, 0.1 to 5 μm, and may have a diameter to length ratio of, for example, 1:1 to 1:30.
[0096] The giant secondary structure obtained in step S10 has a larger particle size than the carbon composite as the final secondary structure, and is therefore called a giant entangled carbon nanotube.
[0097] In one embodiment of the present invention, the entangled carbon nanotube (entangle CNT) is formed by agglomeration of carbon nanotubes that constitute it, and has advantages such as high sphericity, specific surface area, and porosity.
[0098] In one embodiment of the present invention, the sphericity of the entangled giant carbon nanotubes may be, for example, 0.5 to 0.99, specifically 0.6 to 0.95, and more specifically 0.7 to 0.9. The sphericity of the entangled giant carbon nanotubes may be measured by the method described above for the carbon composite.
[0099] In one embodiment of the present invention, the entangled giant carbon nanotubes have an average particle size D of, for example, 20 to 200 μm, 20 to 150 μm, 20 to 100 μm, 20 to 50 μm, 20 to 40 μm, specifically 25 to 35 μm. 50 In one embodiment of the present invention, in order to realize a lithium-sulfur battery with high energy density, a high load positive electrode is necessary, and it may be advantageous to increase the particle size of the sulfur-carbon composite to reduce the amount of binder and conductive material. In this respect, the size of the finally formed porous carbon material (i.e., the secondary structure of carbon nanotubes) may be important. The entangled giant carbon nanotubes as an intermediate structure for forming such a secondary structure of carbon nanotubes may be a structure formed by entanglement of short single carbon nanotubes like a bird's nest. The size of the entangled giant carbon nanotubes may be measured by the method described above for the secondary structure.
[0100] In one embodiment of the present invention, the porosity of the entangled giant carbon nanotubes may be, for example, 60 to 90 vol%, specifically 65 to 88 vol%, more specifically 70 to 85 vol%. The porosity may be measured by a method of ISO 15901:2019 known in the art. When the porosity of the entangled giant carbon nanotubes is in the above-mentioned range, it may have an advantageous effect in terms of internal material transferability of the finally manufactured carbon composite, but the present invention is not limited thereto.
[0101] In one embodiment of the present invention, the specific surface area of the entangled giant carbon nanotubes is, for example, 200 to 400 m. 2 / g, specifically 210-350m 2 / g, more specifically 250-300m 2 The specific surface area of the entangled giant carbon nanotubes can be measured by the methods described above for the secondary structures.
[0102] In one embodiment of the present invention, the entangled giant carbon nanotubes have characteristics of a large specific surface area, high sphericity, and excellent porosity, but when used in an electrode carrying a sulfur-containing compound as an active material, there is a problem that ion diffusion paths are not sufficiently secured. Therefore, the present invention aims to use a secondary structure obtained by modifying the shape of the particles of the entangled giant carbon nanotubes as a porous carbon material.
[0103] To this end, step S20 is a step of obtaining a secondary structure having a modified structure from the obtained entangled giant carbon nanotubes.
[0104] In one embodiment of the present invention, the step S20 may include a step of obtaining a dispersion in which the entangled giant carbon nanotubes obtained above are dispersed in a dispersion medium (hereinafter referred to as a second dispersion medium), and spray-drying the dispersion. In this case, the dispersion may further include a dispersant, and the above-mentioned description of the dispersion medium and the dispersant is used.
[0105] In one embodiment of the present invention, the entangled giant carbon nanotubes may be contained in an amount of 0.1 to 5 wt%, 0.1 to 2 wt%, or 0.5 to 1 wt% based on the total weight of the entangled giant carbon nanotube dispersion. When the weight of the entangled giant carbon nanotubes is within the above range, advantageous effects can be obtained in terms of the particle size and particle size uniformity of the secondary structure to be manufactured, but the present invention is not limited thereto.
[0106] In one embodiment of the present invention, the spray drying method is the same as that described above.
[0107] In an embodiment of the present invention, the step S20 may further include a step of carbonizing after the spray drying. For example, the carbonization may be performed by heating the particles formed by the spray drying in an inert gas atmosphere. The carbonization may be performed, for example, at a temperature of 500°C to 1,200°C, specifically, at a temperature of 500°C to 1,000°C, or at a temperature of 500°C to 800°C for 30 minutes to 5 hours or 1 hour to 2 hours.
[0108] The secondary structure obtained by the above-mentioned method is a secondary structure formed by agglomeration of the above-mentioned carbon nanotubes, and is characterized by having a flower-like structure including a spherical core and at least one amorphous flake on the surface of the core.
[0109] According to yet another aspect of the present invention, there is provided a sulfur-carbon composite using the secondary structure of the carbon nanotube described above as a support for supporting a sulfur-containing compound.
[0110] The sulfur-carbon composite includes the above-mentioned secondary structure and a sulfur-containing compound supported on at least a portion of the interior and exterior surfaces of the pores of the secondary structure.
[0111] The sulfur-containing compound may be used without limitation as long as it can be used as a positive electrode active material in a lithium-sulfur secondary battery. For example, the sulfur-containing compound may include, but is not limited to, inorganic sulfur (S8), lithium polysulfide (Li2Sn, 1≦n≦8), carbon-sulfur polymer (C2Sx)m, 2.5≦x≦50, 2≦m), or a mixture thereof.
[0112] In the sulfur-carbon composite, the sulfur-containing compound may be included by physical adsorption to the secondary structure or by chemical bonding, such as covalent bonding, van der Waals bonding, between elemental sulfur and carbon in the secondary structure.
[0113] In one embodiment of the present invention, the secondary structure and the sulfur-containing compound in the sulfur-carbon composite may be included in a weight ratio of, for example, 1:99 to 99:1. Specifically, the secondary structure and the sulfur-containing compound may be included in a weight ratio of 10:90 to 90:10, 10:90 to 40:60, 10:90 to 50:50, 10:90 to 25:75, 10:90 to 30:70, 15:85 to 30:70, 15:85 to 25:75, or 10:90 to 15:85. When the weight ratio of the secondary structure and the sulfur-containing compound in the sulfur-carbon composite is within the above-mentioned range, the sulfur-containing compound is included in a high content, which can enhance the kinetic activity of the sulfur-carbon composite and can provide an advantageous effect in terms of improving the electrical conductivity of the carbon composite, but the present invention is not limited thereto.
[0114] The sulfur-carbon composite of the present invention includes a carbon composite having a high specific surface area and sufficient ion diffusion paths due to a plurality of internal pores, and thus not only can the sulfur loading amount be increased but also can provide a plurality of active sites for the oxidation / reduction reaction of sulfur. Thus, the sulfur-carbon composite can be used in the positive electrode of a lithium-sulfur battery to improve the battery efficiency and energy density, but the mechanism of the present invention is not limited thereto.
[0115] According to another aspect of the present invention, there is provided an electrode comprising the carbon nanotube substructures described above.
[0116] In one embodiment of the present invention, the secondary structure of the carbon nanotube may be included as a conductive additive in the electrode active material layer of the electrode to improve the electrochemical performance of the electrode, but the present invention is not limited thereto.
[0117] In an embodiment of the present invention, the electrode may have a structure including a current collector and an electrode active material layer on at least one surface of the current collector, or the electrode may be a current collector-free electrode.
[0118] According to another aspect of the present invention, there is provided a positive electrode including the above-described sulfur-carbon composite as a positive electrode active material.
[0119] In an embodiment of the present invention, in addition to the positive electrode active material, the positive electrode may further include, as necessary, a binder, a conductive material, an additive, etc. In this case, specific types of the binder, the conductive material, and the additive may be conventional ones, and therefore, description thereof will be omitted in this specification.
[0120] In another embodiment of the present invention, the positive electrode may include a positive electrode current collector and a positive electrode active material layer in which the positive electrode active material is applied to one or both sides of the current collector together with a binder, but the positive electrode structure is not limited thereto. The positive electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has high conductivity.
[0121] In an embodiment of the present invention, the positive electrode including the sulfur-carbon composite may exhibit excellent effects in terms of sulfur loading amount and sulfur oxidation / reduction reaction activity, but the effects of the present invention are not limited thereto.
[0122] According to yet another aspect of the present invention, there is provided an electrochemical device comprising a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein at least one of the positive electrode and the negative electrode comprises the secondary structure of the carbon nanotube described above.
[0123] According to yet another aspect of the present invention, there is provided an electrochemical device including a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode includes the above-described sulfur-carbon composite as an active material.
[0124] According to an embodiment of the present invention, the electrochemical device may be a lithium-sulfur battery.
[0125] In one embodiment of the present invention, the negative electrode, the separator, and the electrolyte may be used without any particular limitation as long as they are usable in an electrochemical device, particularly a lithium-sulfur battery, within the scope of the present invention, and therefore a detailed description of the specific types thereof will be omitted.
[0126] In an embodiment of the present invention, the electrochemical device may have, for example, a coin type, a cylindrical type, a pouch type, a rectangular type, etc., and the shape of the electrochemical device is not particularly limited. In addition, the electrochemical device may be used not only as a battery cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a plurality of battery cells, and the usage form of the electrochemical device is not particularly limited.
[0127] In an embodiment of the present invention, a lithium-sulfur battery using a positive electrode including the sulfur-carbon composite may exhibit excellent effects in terms of battery energy density, but the effects of the present invention are not limited thereto.
[0128] In one embodiment of the present invention, the lithium-sulfur battery may have an effect of significantly improving energy density by increasing the sulfur loading amount in the electrode and reducing the amount of electrolyte, but the effect of the present invention is not limited thereto.
[0129] Hereinafter, a lithium-sulfur battery using a carbon composite according to an embodiment of the present invention will be described in detail with reference to examples. However, the following examples are merely illustrative of the present invention, and the scope of the present invention is not limited thereto.
[0130] [Fabrication of secondary structures using carbon nanotubes] Comparative Example 1 Fabrication of giant tangled carbon nanotubes Carbon nanotubes with an average diameter of 150 nm (manufacturer: Pyrograf Products, Inc.) were chopped into pieces with an average length of 2 μm using a ball mill with zirconium oxide (ZrO2) balls for 6 hours to produce carbon nanotubes. The chopped carbon nanotubes were dispersed in a 1 wt% polyacrylic acid solution (weight average molecular weight (Mw) of polyacrylic acid: 450,000 g / mol). The amount of carbon nanotubes added was adjusted so that the weight ratio of carbon nanotubes to polyacrylic acid solution was 1:10.
[0131] The dispersion liquid in which the carbon nanotubes were dispersed was spray-dried (conditions: Buchi B-290 mini spray-dryer, inlet temperature 180°C, aspirator 95%, feeding rate 12) to obtain entangled giant carbon nanotubes. The obtained entangled giant carbon nanotubes had an average particle size D 50 30μm, sphericity 0.8, specific surface area 250m 2 / g.
[0132] 1 is a SEM image of the secondary structure according to Comparative Example 1. Referring to FIG 1, it was confirmed that the secondary structure was a secondary particle formed by agglomeration of carbon nanotubes into a spherical shape.
[0133] Example 1 Fabrication of secondary structures The entangled giant carbon nanotubes (secondary particles) obtained in Comparative Example 1 were dispersed in a polystyrene sulfonate solution having a concentration of 18 wt%, and then diluted 5 times with distilled water to prepare a dispersion. The weight ratio of the entangled giant carbon nanotubes:polystyrene sulfonate:distilled water in the prepared dispersion was 18:50:2000.
[0134] The dispersion of the giant entangled carbon nanotubes thus produced was pretreated (HSH (8k / 90 min), followed by tip sonication for 90 min) and fed to a sprayer, where it was spray-dried (conditions: Buchi B-290 mini spray-dryer, inlet temperature 200°C, aspirator 95%, N2 flow 50, feeding rate 15) to form particles, which were then heated and carbonized at 600°C for 2 hours to obtain secondary structures of carbon nanotubes. The secondary structures thus obtained had an average particle size D 50 is 15μm, and the specific surface area is 160m 2 / g.
[0135] Figure 2 is an SEM image of the secondary structure according to Example 1. Referring to Figure 2, it was confirmed that the secondary structure had a flower shape including a spherical core and a plurality of amorphous flakes, specifically, plate-like flakes, formed on the surface of the spherical core.
[0136] [Manufacturing lithium-sulfur coin cells] Example 2 Preparation of sulfur-carbon composites The secondary structure of Example 1 as a porous carbon material and sulfur (S8) were mixed in a weight ratio of 25:75 and reacted at a temperature of 155°C for 35 minutes to prepare a sulfur-carbon composite in which sulfur was supported in the internal pores and on the surface of the secondary structure.
[0137] 5 and 6 are SEM images of the sulfur-carbon composite prepared according to Example 2 immediately after preparation. FIG. 5 is an image at a magnification of 9,000 times, and FIG. 6 is an image at a magnification of 4,000 times.
[0138] Cathode manufacturing A positive electrode slurry composition was prepared by mixing 90 wt % of the prepared sulfur-carbon composite, 5 wt % of denka black as a conductive material, and 5 wt % of styrene-butadiene rubber / carboxymethyl cellulose (weight ratio of SBR:CMC=7:3) as a binder.
[0139] The prepared positive electrode slurry composition was applied onto an aluminum foil having a thickness of 20 μm, and then coated to a thickness of 150 μm using a blade coater, and then dried in an oven at 50° C. to prepare a positive electrode (loading amount 4 mAh / cm 2 ).
[0140] Lithium-sulfur coin cell manufacturing The prepared positive electrode and lithium metal (200 μm thick) as the negative electrode were placed facing each other, a separator (polyethylene with a thickness of 20 μm and a porosity of 45 vol%) was placed between them, and an ether-based electrolyte in which 1.0 M LiFSI and 2 wt % LiNO3 were dissolved was injected to prepare a lithium-sulfur battery.
[0141] Comparative Example 2 A lithium-sulfur coin cell was manufactured in the same manner as in Example 2, except that the secondary structure manufactured in Comparative Example 1 was used as the porous carbon material.
[0142] 3 and 4 are SEM images immediately after the preparation of the sulfur-carbon composite according to Comparative Example 2. FIG. 3 is an image at a magnification of 5,000 times, and FIG. 4 is an image at a magnification of 2,000 times.
[0143] [Performance evaluation of sulfur-carbon composites] From the SEM images of the sulfur-carbon composites in Figures 3 and 4 (Comparative Example 2) and Figures 5 and 6 (Example 2), it was confirmed that the sulfur-carbon composites according to the present invention can form a pore structure that is favorable for ion / electron transport. Together with the experimental results below, it can be inferred that the flower-like appearance including amorphous flakes may show a performance difference in the high-concentration range.
[0144] [Performance evaluation of lithium-sulfur coin cells] Capacity Rating The lithium-sulfur batteries of Example 2 and Comparative Example 2 were measured at 1.7 to 3.0 V (vs. Li / Li) at a current density of 0.1 C at 25° C. using a charge / discharge measuring device (P&E Solution Co., Ltd.). + The capacity characteristics of the battery were evaluated by charging and discharging it three times in the voltage range of 100 V to 200 V. The results of the evaluation of the capacity characteristics of the battery are shown in Figure 7.
[0145] 7, it was confirmed that, although the Comparative Example 2 was capable of exhibiting capacity at 0.1 C, it was inferior to the Example 2 in terms of overvoltage generation.
[0146] Life evaluation The lithium-sulfur batteries of Example 2 and Comparative Example 2 were charged and discharged six times at a current density of 0.1 C at 25° C. using a charge / discharge measuring device (P&E Solution Co., Ltd.), and then charged at a current density of 0.2 C and discharged at a current density of 0.3 C to evaluate the battery life characteristics. The results of the evaluation of the battery life characteristics are shown in FIG.
[0147] 8, it was confirmed that the high rate capacity of Example 2 was far superior to that of Comparative Example 2 under the high rate discharge condition of 0.3C.
Claims
1. A secondary structure in which carbon nanotubes are aggregated, A secondary structure having a flower-like structure comprising a spherical core and at least one amorphous flake on the surface of said core.
2. The specific surface area of the secondary structure is 50 m 2 / g to 1,000m 2 The secondary structure of claim 1, wherein the molecular weight is 1 / g.
3. The average particle size D of the secondary structures 50 The secondary structure of claim 1, wherein the thickness is between 1 μm and 100 μm.
4. The secondary structures have an average grain size D of 10 to 20 μm. 50 A spherical core having an average particle size D of 1 to 5 μm on the surface of the core. 50 and at least one amorphous flake having the formula:
5. 2. The secondary structure of claim 1, wherein the sphericity of said secondary structure is between 0.5 and 0.
99.
6. The total pore volume in the secondary structure is 0.5 to 5 cm 3 The secondary structure of claim 1, wherein the molecular weight is 1 / g.
7. The secondary structure of claim 1, wherein the carbon nanotubes have a diameter of 50-500 nm and a length of 0.1-5 μm.
8. 2. The secondary structure of claim 1, wherein said carbon nanotubes have a diameter to length ratio of 1:1 to 1:
30.
9. (S10) aggregating the carbon nanotubes to obtain giant entangled carbon nanotubes; (S20) obtaining a secondary structure having a modified structure from the entangled giant carbon nanotubes; The secondary structure has a flower-like structure including a spherical core and at least one amorphous flake on the surface of the core.
10. The specific surface area of the secondary structure is 50 m 2 / g to 1,000m 2 The method for producing a secondary structure according to claim 9 , wherein the molecular weight of the secondary structure is 1 / g.
11. The method of claim 9, wherein the step S10 comprises spray-drying a dispersion in which the carbon nanotubes are dispersed in a first dispersion medium.
12. 10. The method of claim 9, wherein the step S20 comprises spray-drying a dispersion in which the entangled giant carbon nanotubes are dispersed in a second dispersion medium.
13. The method for producing a secondary structure according to claim 11 or 12, wherein the first dispersion medium or the second dispersion medium contains water, alcohol, benzene, toluene, pyridine, acetone, tetrahydrofuran (THF), dimethylformaldehyde (DMF), or two or more of these.
14. The method of claim 12 further comprising a step of carbonizing after said spray drying.
15. The method for producing a secondary structure according to claim 14, wherein said carbonization is carried out at a temperature between 500°C and 1,200°C.
16. The method further includes a step of shredding the carbon nanotubes before the step S10, The method for manufacturing a secondary structure according to claim 9, wherein in step S10, a giant entangled carbon nanotube is obtained from the chopped carbon nanotubes.
17. The method for producing a secondary structure according to claim 9, wherein the entangled giant carbon nanotubes have a sphericity of 0.5 to 0.
99.
18. The entangled giant carbon nanotubes have an average particle size D of 20 to 200 μm. 50 The method for producing a secondary structure according to claim 9, comprising:
19. The method for producing a secondary structure according to claim 9, wherein the entangled giant carbon nanotubes have a porosity of 60-90% by volume.
20. The giant tangled carbon nanotubes are 200m long. 2 / g to 400m 2 The method for producing a secondary structure according to claim 9, characterized in that the secondary structure has a specific surface area of 100 / g.
21. A sulfur-carbon composite comprising the secondary structure according to any one of claims 1 to 8 and a sulfur-containing compound supported on at least a portion of the interior and exterior surfaces of the pores of the secondary structure.
22. The sulfur-containing compound is inorganic sulfur (S 8 ), lithium polysulfide (Li 2 Sn, 1≦n≦8), carbon-sulfur polymer (C 2 22. The sulfur-carbon composite according to claim 21, comprising: Sx)m, 2.5≦x≦50, 2≦m), or a mixture thereof.
23. 22. The sulfur-carbon composite of claim 21, wherein a weight ratio of the secondary structure and the sulfur-containing compound is 10:90 to 40:
60.
24. 9. An electrode comprising the secondary structure according to claim 1 in an electrode active material layer.
25. The battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte solution, 9. An electrochemical element, characterized in that at least one of the positive electrode and the negative electrode comprises the secondary structure according to claim 1.
Citation Information
Patent Citations
Lithium ion battery composite anode material and preparation method thereof
CN102244240A
Silicon carbon negative electrode material for power battery and preparation method of silicon carbon negative electrode material
CN108172812A
Carbon-sulfur composite, method for producing the same, cathode and lithium-sulfur battery including the same
JP2019513673A
Titanium oxide-carbon nanotube-sulfur (TiO2-x-CNT-S) composite and its manufacturing method
JP2020534239A
Multipurpose-Cuts-Cuttingboard
KR1020200131638A